Detection of the mecA gene and identification of Staphylococcus directly from blood culture bottles by multiplex polymerase chain reaction - Rocchetti, Taisa Trevizani [UNESP]; Martins, Katheryne Benini [UNESP]; Martins, Patricia Yoshida Faccioli [UNESP]; Oliveira, Rogério Antonio de [UNESP]; Mondelli, Alessandro Lia [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (Elsevier, 2018)
Introduction: Staphylococcus spp. – both S. aureus, including methicillin-resistant strains (MRSA) and coagulase negative staphylococci (CoNS) – are relevant agents of healthcare-associated infections. Therefore, the rapid recognition of MRSA and methicillin-resistant CoNS from blood stream infections is critically important for patient management. It is worth noting that inappropriate empiric therapy has been associated with higher in-hospital mortality. Material and methods: In this study we evaluated a multiplex polymerase chain reaction (multiplex PCR) standardized to detect Staphylococcus spp., S. aureus, and mecA gene-encoded oxacillin resistance directly from blood culture bottles. A total of 371 blood cultures with Gram-positive microorganisms confirmed by Gram-stain were analyzed. Results from multiplex PCR were compared to phenotypic characterization of isolates. Results: Staphylococcus aureus was detected in 85 (23.0%) blood cultures and CoNS in 286 (77.0%). There was 100% agreement between phenotypic and multiplex PCR identification. Forty-three (50.6%) of the 85 S. aureus carried the mecA gene and among the 286 CoNS, 225 (78.7%) were positive for the mecA gene. Conclusions: The multiplex PCR assay developed here was found to be sensitive, specific, rapid, and showed good agreement with the phenotypic results besides being less expensive. This PCR method could be used in clinical laboratories for rapid identification and initiation of specific and effective treatment, reducing patient mortality and morbidity. Furthermore, this method may reduce misuse of antimicrobial classes that are more expensive and toxic, thus contributing to the selection of antibiotic-resistant Staphylococcus spp.
Keywords: Blood cultures; mecA gene; MRSA; Multiplex PCR; Staphylococcus aureus; Staphylococcus spp.